(3GdJTHjgGJs - (3GHf CHj Yhf , EHQGgje Hf eMeO Hf CHj Yhf CMeO Hf GdefLe CHh ESMGb,J (B322 (3g` s
(3ChdgG (B:s
(3RGOc Gddg ai GdBOGH QZHI SCdJfi CYRc Gddg Cf CKHJ dc CHjGJG ef JTHjgGJ GdTYQGA s
(3BNQgG (B:s
(3bGd CHh GSMGb (B: (3bO habfG cJGHfG gPG LejY eG TQWfGg ef fhGOQ GdJTHjgGJ hGdMeO ddg cKjQkG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3LGA HBNQ GdfSNI Cf gPg Cced fSNI hbYJ ai GdJTHjgGJ hGdhQbI GdChdi HNW eZGjQs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs